Survey on Continuous Integration, Deployment and Delivery in Agile and DevOps Practices - Sree Poornalinga, K; Rajkumar, P (International Journal of Computer Sciences and Engineering, 2025)
Innovations pick up the leap and customers desire quick change, business turning out to be progressively more responsive. Ready end product delivery to market is the solution, and to smooth the progress of the overall business aspiration, software life cycle process needs to be fast. Over the years the transition from waterfall model to agile methodology has come into the era. Progressions of these development operations are moving towards the downstream with the evolution of DevOps. Deployment of software applications in a trustworthy, repeatable, and reliable approach meet up the demands of an agile development which can only be completely achieved by embracing automation. Several DevOps main beliefs are supported by Amazon Web Services (AWS) which every IT departments can profit fromand thus business agility is improved. In this paper, we focus on delivering the principles of DevOps and Continuous Integration, Deployment and Delivery practices supported by them.